The Role of Systemic Hemodynamic Disturbances in Prematurity-Related Brain Injury - du Plessis, Adré J. (2009)
Premature infants who experience cerebrovascular injury frequently suffer acute and long-term neurologic complications. In this paper, we explore the relationship between systemic hemodynamic insults and brain injury in this patient population and the mechanisms that might be at play.